Climate treaties and approaching catastrophes. - Barrett, Scott (Journal of Environmental Economics & Management, 2013)
Abstract: If the threshold that triggers climate catastrophe is known with certainty, and the benefits of avoiding catastrophe are high relative to the costs, treaties can easily coordinate countries' behavior so as to avoid the threshold. Where the net benefits of avoiding catastrophe are lower, treaties typically fail to help countries cooperate to avoid catastrophe, sustaining only modest cuts in emissions. These results are unaffected by uncertainty about the impact of catastrophe. By contrast, uncertainty about the catastrophic threshold normally causes coordination to collapse. Whether the probability density function has “thin” or “fat” tails makes little difference.